Impact : vol. 1, no. 5, August, 1943. - United States. Army Air Forces (Washington, D. C. : Office of the Assistant Chief of Air Staff, Intelligence, 1943)
Impact is a medium for the dissemination, in graphic form, of air intelligence and correlated subjects. It presents information on the results of our operations against the enemy. So that Air Force units in one theater may be informed of how units in another meet specific problems, pertinent data on the operations themselves is also included. Contents: Battle for the Islands; ATC over South Atlantic; P-38 Formation Vs. Zeros; Bombs-through Air and Water; Naval Base and Rubber Plant Hit; Photo Sermon on Air Safety; For the Photo-Interpreter; AFCE in Burma; Sub Problems in Mediterranean; Photo Bomb Reveals Jap Field; Attu, from Air and Ground; Italian Islands, then Mainland; New Way of Adding Dimension.